PENGARUH KUALITAS PELAYANAN, BUDAYA ORGANISASI, KEPUASAN KERJA, DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI PT. MUTIARA MULTI FINANCE TANGERANG - Komalasari, Ros; Dirgantara, Febri; Pramukty , Rachmat (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
This Study aims to determine the effect of service quality, Organizational culture, job statisfaction, and their impact on employee performance PT. Mutiara Multi Finance Tangerang. This Study uses the data deskriptif Then analysis using correlation analysis and multiple linier regression. Based on test result found that the variable quality of service significantly influence employee performance, Great influence on employee performance quality of service for the amount 17,1%. 0,17. Based on t test result found that thevariable of organizational culture has a major influence magnitude 0,124 or 12,4%. Based on the test results of the variable t is known that job statisfaction has a magnitude of 0,202 magnitude of the effect of 2,02%, but the figure does not affect the performance of employees at an error rate of 5%. Result of the study were seen from R2 value of 0,268 or 26,8% indicate that the independent variables consist of quality of service, organizational culture, job statisfaction can contribute a great influence on the performance of employees at 26,8% while the remaining 73,2% explained by other factors not included in the research model. This Study aims to determine the effect of service quality, Organizational culture, job statisfaction, and their impact on employee performance PT. Mutiara Multi Finance Tangerang. This Study uses the data deskriptif Then analysis using correlation analysis and multiple linier regression. Based on test result found that the variable quality of service significantly influence employee performance, Great influence on employee performance quality of service for the amount 17,1%. 0,17. Based on t test result found that thevariable of organizational culture has a major influence magnitude 0,124 or 12,4%. Based on the test results of the variable t is known that job statisfaction has a magnitude of 0,202 magnitude of the effect of 2,02%, but the figure does not affect the performance of employees at an error rate of 5%. Result of the study were seen from R2 value of 0,268 or 26,8% indicate that the independent variables consist of quality of service, organizational culture, job statisfaction can contribute a great influence on the performance of employees at 26,8% while the remaining 73,2% explained by other factors not included in the research model.